The Australia-New Zealand connection re-visited, with two new species of Cartomothrips (Thysanoptera, Phlaeothripinae) - Mound, Laurence A.; Walker, Annette K. (Zootaxa, 2012)
The distribution of the six species in Cartomothrips is considered, and a key provided for their identification. C. tofti sp.n. is described from New Zealand; manukae is widespread in New Zealand but also found in Tasmania; neboissi is infrequent in New Zealand but common in southern Australia; laughlini is known only from South Australia; browni breeds in the seed capsules of some Eucalyptus species and thus presumably is an Australian species but has also been found in Brazil, California, Kenya and New Zealand; C. abrsi sp.n. is described from Tasmania.